Sharia-Based Human Resource Management: Implementation of Islamic Values in Employee Management at LKP English Academy Bengkulu - Ade Riska Nur Astari (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2024)
Background: This study aims to explore the implementation of Islamic values ​​in human resource management at LKP English Academy Bengkulu and its impact on employee performance and well-being. Method: The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation analysis. Results: The distribution of informants' positions shows that the majority are teaching tutors (86%), with directors, academic managers, administrative staff, and facilities and infrastructure staff each accounting for 100%. Conclusion: The implementation of Islamic values ​​at LKP English Academy Bengkulu creates a fair, transparent, and humane work environment, which ultimately improves overall organizational performance.